2019
DOI: 10.1177/0271678x19874643
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of simultaneous arterial spin labeling MRI and 15O-H2O PET measurements of regional cerebral blood flow in rest and altered perfusion states

Abstract: Arterial spin labelling (ASL) is a non-invasive magnetic resonance imaging (MRI) technique that may provide fully quantitative regional cerebral blood flow (rCBF) images. However, before its application in clinical routine, ASL needs to be validated against the clinical gold standard, 15O-H2O positron emission tomography (PET). We aimed to compare the two techniques by performing simultaneous quantitative ASL-MRI and 15O-H2O-PET examinations in a hybrid PET/MRI scanner. Duplicate rCBF measurements were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…Similar benefits are expected in comparing OEF by the two modalities, especially if multiple physiological states are observed, e.g. after vasodilation ( Puig et al, 2019 ). Furthermore, global OEF MRI measurements from the superior sagittal sinus are more widespread and have been compared to each other with some success ( Barhoum et al, 2015 ).…”
Section: Comparison With Mri and Opportunities With Simultaneous Pet/mentioning
confidence: 58%
“…Similar benefits are expected in comparing OEF by the two modalities, especially if multiple physiological states are observed, e.g. after vasodilation ( Puig et al, 2019 ). Furthermore, global OEF MRI measurements from the superior sagittal sinus are more widespread and have been compared to each other with some success ( Barhoum et al, 2015 ).…”
Section: Comparison With Mri and Opportunities With Simultaneous Pet/mentioning
confidence: 58%
“…The results revealed no notable differences in the gCBF or rCBF for the areas under the electrodes from the different tDCS intensities (Figure 2). We did not find any immediate effects (i.e.,~1-2 min post-stimulation) of tDCS on CBF in this functional [ 15 A battery-operated tDCS device (Soterix Medical Inc., New York, NY, USA) administered the stimulation. A previous study indicated that 5 min of tDCS over the primary motor cortex (M1) was sufficient to induce significant increases in MEP amplitude and that the effects of the stimulation returned to baseline after 10 min [16], and another study indicated significant blood flow changes from 4 min of motor cortex stimulation [17].…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a pilot investigation on the effects of tDCS on CBF with semi-quantitative [ 15 O]water Positron Emission Tomography (PET), the gold standard for CBF measurements [11][12][13][14][15], in a sample of three people with relapsing-remitting MS (Table 1). Scans were completed in two blocks, one at baseline and five immediately after randomized tDCS stimulation intensities (1, 2, 3, 4 mA, and sham; six scans per block).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, post-recanalization perfusion was evaluated by means of arterial spin labeling (ASL), a non-invasive MR-based technique that provides truly quantitative perfusion maps without the limitations of contrast agents 23,24 and that has been validated against conventional methods in both healthy controls and AIS patients. 2530…”
Section: Introductionmentioning
confidence: 99%